PEMBANGUNAN INDONESIA DALAM PANDANGAN AMARTYA SEN - Sri Henny Indarti (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2017)
Abtsract: Balancing of materialistic and non-materialistic factors for human welfare, hard concern for the distribution of opportunities within society was important thing for realize development. Increasing income can be used as a part of development without reliable indicator of freedom as substantial factor. There’s 3 process who must be reached by all of one, such as increasing change of distribution basic needs, increasing living standart by increase income, increasing education quality and the concern for cultural of values. This article just talking about that it’s not eazy to a realized but we have to learn by Amartya Sen perspective. Keywords: Development, Social Change, Capability, Amartya Sen, Perspective Abstrak: Keseimbangan faktor materi dan non materi untuk kesejahteraan manusia, penekanan terhadap kesempatan distribusi dalam masyarakat merupakan hal penting untuk merealisasikan pembangunan. Peningkatan income tidak dapat dijadikan bagian dari pembangunan tampa merealisasikan indikator kebebasan sebagai faktor substansi, disamping peningkatan kualitas dan memperhatikan nilai-nilai budaya. Kata kunci: Pembangunan, Sosial, Kapabilitas Amartya Sen